When insect development meets insect succession: Advantages of combining different methods and insect taxa in estimating the post-mortem interval - Szymon Matuszewski; Anna Mądra-Bielewicz (Forensic Science International: Synergy)
Insects are frequently used to estimate post-mortem interval (PMI). Experts usually base their estimates on a single insect taxon and use a single estimation method, even if multiple taxa are present on a cadaver or multiple methods can be applied. In this article we present a case report where multiple insect evidence and methods were used in a homicide case to estimate PMI. Since the true PMI was known, we were able to assess the estimation errors of each method as applied to particular insect evidence. The final grand PMI was derived from a developmental estimate based on third instar larvae of Lucilia illustris/L. caesar species group and a successional estimate based on adult Thanatophilus rugosus beetles. By averaging these estimates we got the grand PMI of almost perfect accuracy (1 % relative error, PMI range: 4.39 ± 0.77 days), which is of course an exceptional situation for entomological methods of estimating PMI. Furthermore, this was the first case report in which the presence and absence of subsequent life stages of carrion insects coupled with the estimation of their pre-appearance interval were used to estimate the PMI range. The results regarding the minimum PMI were fully consistent with the results obtained using the classical developmental method. This finding indicates that in some cases the presence/absence method can be used interchangeably with the developmental method. Finally, we discussed the prospects and limitations of combining insect evidence and methods of their analysis in estimating PMI.